A systematic review on online gaming addiction and student's behaviour in gaming: the case of playerunknown's battlegrounds (PUBG) / Wardatul Hayat Adnan and Ateefa Azairi - Adnan, Wardatul Hayat; Azairi, Ateefa (Universiti Teknologi MARA, 2021)
Online gaming addiction issues are very popular among students until now. Previous study shows that previous researchers are more focusing on the online gaming addiction. Less research was conducted in the effect of the addiction on the students' behaviour. However, as for present study, the researcher will be focusing on online gaming addiction and students' behaviour in Malaysia. Previous research shows data about 1.4% addicted to online gaming and experiencing negative behaviour issues. Moreover, online gaming also led to a negative behaviour because of the extreme elements in the game. Therefore, the target of the present study is to do a systematic review on online gaming addiction and student's behaviour in gaming the case of PUBG. The present study will employ a Qualitative method. PRISMA systematic review will be conducted in reviewing previous journals starting from the year of 2016 until 2020. Findings show that the addiction of PUBG among the students in Malaysia results in a negative behaviour amongst them. This data can justify why behaviour issues among students in Malaysia keep on rising. A collective of systematic review assists in identifying the trends on online gaming addictions and students' behaviour in gaming.